Research on Buckling and Post-buckling Characteristics of Composite Curved Stiffened Fuselage Panel under Hoop Bending load. (September 2019) - Hao, C; Nan, C Y; Peng, Z; Lei, L
Abstract: In order to study the buckling, post-buckling and failure modes of composite fuselage structures under circumferential bending loads, innovative four-point bending tests technology was developed and performed on composite curved stiffened fuselage panel (CSFP) specimens with two frame configurations of C-section and Z-section. Meanwhile, the stability engineering analysis and estimation based on plate buckling theory and simplified boundary were carried out, and the finite element (FE) models based on Hashin failure criterion were established to simulate the buckling, post-buckling and failure modes of CSFP specimens. The tests and analysis results show that the buckling modes and failure modes of C-section and Z-section specimens are different under positive bending loads. Specifically, the buckling of C-section specimens firstly occurs in the middle of the frame, then local buckling occurs at both ends of the frame, leading to fracture. For Z-section specimens, only local buckling occurs in the middle of the frame, which directly leads to fracture. By comparing the three methods, the results of FE analysis and engineering calculation are in good agreement with the test results. Among them, the prediction of instability mode and failure mode by FE method is very accurate, and the buckling strain calculated by engineering method can provide a good reference for structural design.